Transitioning from an Historical to a Contemporary Use of Tax Record Data for Measuring Top Incomes in Australia. Issue 2 (16th April 2018) - Burkhauser, Richard V.; Hahn, Markus H.; Wilkins, Roger
Abstract : A major literature using tax data measures the share of income captured by the top of the income distribution. We correct existing Australian estimates by removing employers' social contributions from the denominator and explain the limitations of using public record tax tables to capture the numerator. We show that Australian Tax Office unit record sample data are only able to accurately measure incomes of top income groups below the top 1 per cent. We conclude that greater access to the entire unit tax record population will be necessary to bring Australian research in this area up to that in the United States and United Kingdom.